COMPARATIVE ANALYSIS OF THE ORGANIZATION OF FINANCING OF SCIENTIFIC AND RESEARCH WORKS ON THE EXAMPLE OF THE RUSSIAN FEDERATION, WESTERN EUROPE AND ASIA - R. A. Alandarov; K. O. Tarkhanovsky (Финансы: теория и практика, 2017)
Topic. The article presents a review of existing approaches to the funding of science in the various countries of the world. The system of financing scientific research is a complex of legal, financial and administrative measures aimed at creating an effective infrastructure allowing for high performance of basic research and applied design and experimental works as well.Purpose. The purpose of this paper is a comprehensive analysis of the peculiarities of financing of scientificresearch and experimental-design works in the Russian Federation and justification of the choice on the basis of this study, the most suitable for Russian reality approach to the formation of mechanisms of research funding. To achieve the addressed purpose we performed the following tasks: analysis of the working principles and characteristics of each approach; a comparative analysis of the application of these approaches on the example of Western Europe, Asia, and the Russian Federation.Methodology. The methodological basis for this research were economic-statistical, systematic, and comparative analysis methods.Results. This article discusses and analyzes in details the main approaches to financing scientific-research and experimental-design works — Newtonian, Baconian, and Jeffersonian. It is presented the essence of selected approaches, their advantages and disadvantages, examples and statistical data from practices of different countries.Conclusions. Based on comprehensive analysis of statistical data, the authors recommend to the appropriate executive and legislative authorities of the Russian Federation to begin the transformation of the instruments of financing of scientific-research works in the direction of Jeffersonian approach, i.e. to develop program funding and grants for scientific research for civilian use.